The Effect Of Consumption Of A High-Purine Diet On Increasing Uric Acid Levels And Blood Pressure In The Elderly In Kediri District - Hariyono, Hariyono; Peristiowati, Yuly; Arantriwardhani; Endah Pujiati; Andariningsih; Yulida Ti'ani; Tutik Nusnah; I'im Murtiawani; Asri Dewi Wahyuningtyas; Joko Sutrisno (Journal for Research in Public Health, 2024)
High purine consumption is a factor that is closely related to hyperuricemia. Apart from that, hyperuricemia is also closely related to the occurrence of increased blood pressure (hypertension). The aim of this research is to determine the effect of consuming a high purine diet on increasing uric acid levels and blood pressure in the elderly in Kediri Regency. The research method used was observational analytics with a cross sectional design. The research results in this study are that there is a significant influence between a high purine diet and uric acid levels and blood pressure in the elderly in Kediri Regency. This can be seen from statistical tests using Linear Regression, which showed a significant influence of Sig (2-tailed) between high purine diet consumption and uric acid levels (DP-AU=0.000) with a value of α≤0.05, there was a significant influence of Sig. (2-tailed) between Uric Acid Levels and Increased Systolic Blood Pressure in the elderly (AU-TS=0.028) and diastolen blood pressure (AU-TD = 0.032) with a value of α≤0.05, meaning the hypothesis is accepted that there is a significant influence Between a high purine diet and uric acid levels and blood pressure in the elderly in Kediri Regency. Excessive intake of a diet high in purine causes the accumulation of purine crystals to build up in certain joints which can increase uric acid levels in the blood. High uric acid levels can cause increased blood pressure through the mechanisms, inflammation of the kidneys and endothelium, activation of the renin-angiotensin system, depletion of nitric oxide, proliferation of smooth muscle cells, formation of superoxide, mitochondrial dysfunction, and activation of the polyol pathway.